2021
DOI: 10.1016/j.isci.2021.102313
|View full text |Cite
|
Sign up to set email alerts
|

Replication-stress-associated DSBs induced by ionizing radiation risk genomic destabilization and associated clonal evolution

Abstract: Replication-stressassociated DSBs accumulate after exposure to ionizing radiation Such DSBs risk genomic destabilization and associated mutagenesis The resulting genomic rearrangements and mutations lead to clonal evolutionThe radiation-associated risks arise at wide ranges of radiation doses and dose rates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…A previous in vitro study revealed a correlation between induction of SVs and SNVs within the 1-10 Mb range 17 . To examine SNV induction rates near SV sites in cancer cells directly, the number of SNVs within 1 Mb of an SV site was counted and compared with the random number expected (Fig.…”
Section: Sv-associated Mutagenesis (Snv Induction)mentioning
confidence: 91%
See 3 more Smart Citations
“…A previous in vitro study revealed a correlation between induction of SVs and SNVs within the 1-10 Mb range 17 . To examine SNV induction rates near SV sites in cancer cells directly, the number of SNVs within 1 Mb of an SV site was counted and compared with the random number expected (Fig.…”
Section: Sv-associated Mutagenesis (Snv Induction)mentioning
confidence: 91%
“…The ICGC PCAWG study was searched for validated data on SVs, SNVs, insertion/deletions (indels), mutational signatures, and clinical data (sex, age at diagnosis, and survival time) in patients with breast (BRCA-EU, BRCA-UK), ovarian (OV-AU), pancreatic (PACA-AU, PACA-CA), gastric (GACA-CN), liver (LICA-FR, LINC-JP, LIRI-JP) and prostate (PRAD-CA, PRAD-UK) cancers, and in patients with pancreatic endocrine neoplasms (PAEN-IT, PAEN-AU) and chronic lymphocytic leukemia (CLLE-ES) 18 . Validated data on SVs and SNVs in mouse embryonic fibroblast cells (MEFs) were obtained from a previous study 17 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation between individual radiosensitivity and SNPs in the BER genes ( LIG1 and NEIL1 ) or DNA repair genes in the NHEJ pathway ( XRCC5 , XRCC6 and XRCC7 ) was reported in human peripheral blood cells of a population exposed to chronic low-level radiation [ 134 ]. Notably, a genomic destabilization has been observed in mouse embryonic fibroblasts after the repair of radiation-induced DSBs due to replication stress-induced DSB accumulation caused by oxidative DNA damage [ 135 ]. Under this condition, cells were more prone to develop single nucleotide variants (SNV), including radiation-associated SNVs.…”
Section: Genetic and Epigenetic Changes Associated With Radiation Carcinogenesis Riskmentioning
confidence: 99%